Contributions of Annex SL to Corporate Sustainability - Nunhes, Thaís Vieira; Campos, Thalita Láua Reis; Francisco, Fernanda Ellen; Oliveira, Otávio José de (Frontiers in Sustainability, 2021)
With the advance of globalization and population increase, it was necessary to intensify the production of goods to meet the new demands that arose. As a result, a significant emergence of negative socio-environmental impacts was observed, affecting the entire planet. The UN launched the 2030 Agenda to encourage all sectors of the economy, including the industrial sector, in promoting Sustainable Development (SD). Companies have sought to adopt techniques, tools, and practices that enable SD in organizations. Among the range of possibilities to operationalize sustainable management, there are the Certifiable Management Systems (CMSs) ISO 9001, ISO 14001, and ISO 45001. In order to facilitate the integration between these systems, ISO launched in 2018 the Annex SL with the High-Level Structure (HLS), providing greater compatibility between them. However, most companies do not know enough about this change and its benefits for sustainability. Thus, this work presents the main contributions of Annex SL to the development of sustainability in companies that have implemented CMSs. By reviewing the literature on the relationship between CMSs and sustainability, and the expertise of the authors, it was possible to identify and discuss the contributions of the main elements of the HLS to sustainability, which are organizational context analysis, risk management, evidence-based decision making, emphasis on measuring and evaluating processes and results, and culture of integration and continuous improvement.